In-Vivo Digestibility of Rice Straw Silage Added With Buffalo Rumen Microbes In Ongole Cross Breed - Bestari, John; Thalib, Amlius; Hamid, H; Suherman, D (Indonesian Journal of Animal and Veterinary Sciences, 1999)
An experiment was cunducted to investigate the effect of rice straw silage added with buffalo rumen microbes on the in-vivo nutrient digestibility in Ongole cross breed. Twelve male young cattle (222 + 14 kg) were distributed into 3 groups, with 4 animals in each group. The dietary treatments were : Elephant grass (R1) fresh rice straw (R2) and rice straw silage added with buffalo rumen microbes (R3). Grass and concentrate were given at 2.25% of live weight. The experiment was conducted for 15 weeks in Ciawi using total collection and arranged in a Completely Randomized Design. The results showed that digestible DM and OM intakes of R3 was 6882 and 5974 g/head/day which was not significantly different from R1 (6905 and 6188 g/head/day) but significantly different from R2 (6654 and 5588 g/head/day). The digestible protein intake of R3 was 905 g which was higher than R2 (827 g)(P < 0.05). Intake of digestible protein of R1 (951 g/head/day) was 46 g higher than R1 (P > 0.05) and 124 g higher than R2 (P < 0,05). DM and OM digestibilities of R3 (i.e. 68.16% and 78.02%) were significantly higher than R2 (61.79% and 71.58%) but similar to R1 (66.34% and 76.37%). Digestible neutral detergent fiber (NDF) and fat intake were different among each treatment. In conclusion, rice straw silage added with buffalo rumen microbes has a similar nutritive value as elephant grass when fed to Ongole crossbreed cattle. Â  Key words : Rice straw silage, microbe, digestibility